Konsep Desain Perpustakaan Umum Kota Sukabumi dengan Pendekatan Arsitektur Sunda - Indra Suwarna (Fakultas Teknik - Universitas Bung Karno, 2023)
This research raised the design of the Library Building in Sukabumi City with a Sundanese Architecture approach. This Library Building has a function as an educational space that can increase public literacy interest, accommodate learning activities to find information and recreation for the community. The architectural design concept of this library refers to the locus design approach with traditional Sundanese architecture. The research method used is an exploratory qualitative method in order to get shape in architectural design. From the results of the discussion of the architectural design of the Sukabumi City Public Library building in accordance with the Neo Vernacular approach which applies the concept of mass composition of the Kasepuhan Ciptagelar Cisolok traditional settlement, starting from the foundation of Sundanese architectural cosmology.